Harnessing HVAC Exhaust Airflow for Small-Scale Wind Energy Generation: A Novel Approach to Renewable Power Recovery - yogi priyo istiyono; Gaguk Firasanto; Dede Russandi (PROtek : Jurnal Ilmiah Teknik Elektro, 2026)
The increasing global population has significantly elevated the demand for electrical power. As conventional energy resources are finite, the need for alternative and sustainable energy solutions becomes more pressing. This study explores the potential of harnessing HVAC exhaust airflow for small-scale renewable energy generation. Experimental results show an average airflow velocity of 6.14 m/s producing a stable 217 V AC output under a 50 W load. However, the system’s power output remains modest and highly dependent on air conditioner operation cycles, which limits scalability and consistent energy supply. These findings highlight the practicality of energy recovery from existing HVAC systems, although improvements in turbine design, duct geometry, and energy storage are necessary to enhance efficiency and real-world integration.